A Potential Practices of Vendor Managed Inventory Elements in Construction Industry - Radzuan, Kamaruddin; Rahim, Mohd Kamarul Irwan Abdul; Yaakob, Mazri; Anuar, Herman Shah; Osman, Wan Nadzri; Ahmad, Md Fauzi (CENTRAL ASIA AND THE CAUCASUS, 2024)
The construction industry plays an important role in developing infrastructure needs for socio-economic development as well as contributing to economic growth. However, there are some obstacles including weaknesses in terms of level of logistics competence, information sharing efficiency with suppliers as well as poor inventory management. In line with the principles and practices of inventory management (IM), the construction industry needs to consider the best practices to improve the efficiency and effectiveness of its entire supply chain. The study used qualitative approach, which data were gathered from semi-structured questions through interview process. There are two companies involved in this overview study of IM practices, which include a manufacturer of construction building component and a contractor. The finding shows that replenishment decisions, inventory ownership, inventory location, distribution model and information sharing practices are quite similar with VMI practices. Based on the findings, construction industry has high potential to implement VMI practices. Since, project process is unique and always requires new design of VMI, manufacturer, developer and contractor should consider quantity and size of component in designing their VMI practices